F6 Does premanifest HD perform worse in arithmetic? Symbol digit and calculation tests confirm early cognitive impairment in preHD and correlate with brain MRI abnormalities. (13th September 2016) - Castaldo, Anna; Nanetti, Lorenzo; Bachoud-Lévi, Anne-Catherine; Giavazzi, Maria; Contarino, Valeria; Nava, Simone; Mongelli, Alessia; Gellera, Cinzia; Grisoli, Marina; Bruzzone, Maria Grazia; Bella, Daniela Di; Ciammola, Andrea; et al.
Abstract : Objectives: We aimed to identify markers of cognitive and structural brain abnormalities in premanifest Huntington's disease subjects (preHD). Participants and methods: We enrolled 29 preHD (13F/16 M, age 36.5 years, CAG range 37–48; UHDRS-TMS <5) and 25 sex-age matched controls (14F/11 M, age 35.7 years). Subjects underwent 3 Tvolumetric brain MRI (Philips Achieva). Anatomical data were segmented with FreeSurfer. The cognitive battery included: MMSE, Calculation test, Stroop, Verbal fluency, Symbol Digit Modalities Test (SDMT), Trail Making Test, Attentive Matrices test, Digit Span forward and reversal. Estimated years-to-onset were obtained using Langbehn's method. Results: PreHD and controls did not differ in total intracranial volume, caudate volumes, and cortical thickness, and presented scores within normal range in all cognitive tests. However, preHD scored significantly worse than controls in SDMT (p = 0.048), in MMSE (p = 0.0013) and in Calculation test (p = 0.014). Analyses of sub-item of the Calculation test showed that preHD, and in particular the group of close-to-onset preHD (−16 years), made specifically more mistakes than controls in the subtraction task (p = 0.0089), while preHD and controls did not differ in multiplications. The SDMT score correlated with left occipital cortical thickness (p = 0.0029) and Calculation test total score with caudate nucleus volumes (p = 0.032). Conclusions: We confirm that SDMT can identify very early abnormalities in preHD and the scores directly correlate with occipital cortical thickness. The results of the Calculation test suggest that preHD have selective executive deficits in calculation, as demonstrated in the subtraction process, while in the multiplication task, implying mainly memory retrieval, no differences were found.